The Role of Sociolinguistics in Teaching Arabic for Non-Native Speakers: في تعليم العربية للناطقين بغيرها (Linguist, 2026)
This study seeks to clarify the role of sociolinguistics in teaching of foreign languages, taking the teaching of Arabic as an example and model. To achieve this aim, the study is divided into three sections. The first section, “General Introductions,” presents a number of theoretical and methodological preliminaries that demonstrate the importance of sociolinguistics in the study of language from the perspective of its relationship with social variables and the social organization of the environment in which it is used, as well as the effects of this reciprocal relationship on teaching the mother tongue and foreign languages.The second section, “Sociolinguistics and Language Teaching,” addresses the ways in which sociolinguistic theory can be transformed into diverse applications in foreign language teaching. This section focuses on sociolinguistics as a linguistic theory that explains language acquisition and learning on the one hand, and as a field of knowledge that offers profound insights and perspectives into the contexts of language teaching, teaching methods, and designing teaching materials on the other.The third section, “Sociolinguistics and Teaching Arabic to Non-Native Speakers: Concepts and Applications,” presents a direct application of sociolinguistic concepts to the teaching of Arabic to non-native speakers and to curriculum design. It discusses three concepts and clarifies their applications: exposure, interaction, and linguistic borrowing.The conclusion reveals the importance of sociolinguistics in theorizing methods of foreign language teaching and their instructional contexts, as it is the field of knowledge that uncovers the social environment and its interactive contexts.
Keywords: Sociolinguistics; Language Exposure; Interaction; Arabic as Second Language; Communication